Portrait of Educational Institutions Under Muslimat Education Foundation (YPM) at Kediri: In Quality Improvement Management - Hanani, Nurul (Didaktika Religia, 2018)
This study intends to explain the portrait of educational institutions fostered by Muslimat Education Foundation (YPM) NU in Kediri Regency, and try to describe the effectiveness of Muslimat NU in Kediri Regency in improving quality. This study seeks to describe in depth the problems in accordance with the data obtained in the field and on the interpretation of researchers. Muslimat NU is one of the organizations of many organizations in the community. Muslimat NU is a community organization and is an autonomous body of Nahdlatul Ulama whose task is helping to implement policies on women members. Among YPM's work programs in order to improve the quality of education in the district of Kediri are improving the quality of Al-Qur'an Kindergarten and play group, including on managerial aspects, facilities and infrastructure, administration, curriculum and Human Resources (teachers, managers and employees).